Chinese Australians : politics, engagement and resistance - Couchman, Sophie; Bagnall, Kate (Brill, 2015)
In Chinese Australians: Politics, Engagement and Resistance key scholars of Chinese-Australian history explore how Chinese Australians in the nineteenth and twentieth centuries influenced the communities in which they lived on a civic or individual level.